A cannabidiol-sensitive region involved in the allosteric modulation of the α7 nicotinic receptor - Juan Facundo Chrestia; Franco Viscarra; Philip C. Biggin; Isabel Bermudez; Cecilia Bouzat (Proceedings of the National Academy of Sciences, 2026)
Cannabidiol (CBD), a nonpsychoactive phytocannabinoid from Cannabis sativa , modulates the α7 nicotinic acetylcholine receptor (α7 nAChR), a key target in neurological, neurodegenerative, and inflammatory disorders. However, the molecular basis of this modulation remains unresolved. By combining single-channel recordings, molecular dynamics (MD) simulations, and targeted mutagenesis, we identify an allosteric region governing CBD action. CBD produces a marked inhibition of α7 channel activity, followed by a recovery phase characterized by infrequent prolonged openings. MD simulations in closed and desensitized conformations reveal partially overlapping putative CBD-binding sites at the extracellular end of the transmembrane domain. Mutations in M1 and M4 residues within these sites differentially reshape CBD modulation: Some attenuate its inhibitory action, whereas others potentiate the increase in open-channel duration. Strikingly, the M4-L487A mutation converts CBD into a strong positive allosteric modulator, demonstrating that subtle perturbations of this region can invert the direction of modulation. Functional outcomes do not map to discrete sites, indicating that CBD engages an extended allosteric network involved in CBD dual modulation. These findings identify a CBD-sensitive regulatory region, define molecular basis of α7 modulation by CBD, and provide a framework for designing next-generation modulators of pentameric ligand-gated ion channels.